Man and urban living today - Price, Robert David, 1931- (Westchester, Ill. : Benefic Press, 1974)
Discusses the growth and importance of cities throughout history and explores such aspects of urban life as city government, transportation, drug abuse, and minorities.
Keywords: Cities and towns -- United States -- Juvenile literature; Social problems -- Juvenile literature; Cities and towns; Social problems; United States -- Social conditions